Water in times of climate change : a values-driven dialogue - Hasselaar, Jan Jorrit; IJmker, Elisabeth (Amsterdam University Press B.V., 2021)
"This book on water and climate change goes beyond the usual and predictable analyses, by bringing religion and values into a discussion that is often dominated by technocratic solutions. The three case studies of Jakarta, Cape Town, and Amsterdam demonstrate the challenges of water management in urban areas and the role religion can play in addressing them. With representatives from science, politics, economics, and religion, as well as young voices, the book stimulates a values-driven dialogue on issues of water in times of climate change."--PRovided by publisher